Isolation of apigenin-7-O-(6''-O-E-caffeoyl)-β-D-glucopyranoside from Leucas aspera L. with anti-inflammatory and wound healing activities - Rajamanickam Manivannan (GarVal Editorial Ltda., 2016)
Context: Leucas aspera L. (Labiatae) is a common aromatic herb and grows generously in South India and in the broad area of South Asia. Traditionally, this species is taken orally for analgesic, anti-inflammatory, anti-bacterial and wound healing treatments. Aims: To isolate compounds from L. aspera with anti-inflammatory and wound healing activities. Methods: The chloroform extract was subjected to a column chromatography on silica gel 60 and their structures were established by spectral analysis (UV, IR, and NMR). The anti-inflammatory activity of the test compounds was evaluated in male albino rats. The acute inflammation was induced by the subplantar administration of 0.1 mL of 1% carrageenan in the right paw. The excision wound model was used to study the rate of wound contraction and the time required for complete epithelization of the injuries in rabbits. Results: A flavonoid apigenin-7-O-(6"-O-E-caffeoyl)-β-D-glucopyrano-side (1) was isolated from a chloroform fraction of L. aspera. The hydrolysis of compound 1 yield an apigenin (aglycone), caffeic acid and β-D-glucose. Assuming caffeoyl glucose linked to the 7-OH group of apigenin. Conclusions: Compound 1 exhibited a significant anti-inflammatory activity compared with standard diclofenac sodium. The wound healing study revealed that decreased wound area and significant increase in epithelialization in treatment groups was observed.